An exploration of lived experiences of 11 resettled families in Mazabuka district, Zambia, by a Nickel mine project - Tumbama, Lewis (Department of Chemical Engineering, 2020)
Mining-induced displacements and resettlements are a global phenomenon. However, how these are done and the implications that they have on the displaced and resettled are shaped by micro, local level dynamics. These include existing regulations, socio-economic and cultural situations of communities involved, level and type of compensations offered to the communities, among others. These shape how communities live the experiences of being displaced and resettled, as more powerful companies with financial resources seek out mining opportunities. For communities that are displaced and resettled, this process becomes a socio-economic one as change of place has implications on people’s ability to access resources on which they depend. This may lead to a transformation of their livelihood assets in the short and long term, which requires changing of their livelihood strategies. Zambia is endowed with natural resources, and the mining sector is the mainstay of the country’s economy. In particular, Zambia ranks among the top 15 producers of copper in the world. The government of Zambia (GRZ) gives mining licenses to companies that in return, pay royalties in form of taxes that support the government’s development programs nation-wide. Therefore, mining is said to be in the broader interest of the nation (GRZ, 2006). This means that the rights to the access and use of land by a particular group of people, individuals or ethnic grouping will be superseded by an economic undertaking that is seen as having a broader development interest of the nation. This includes economic activities such as building bridges or hydro-electric plants, road construction, building economic zones and mining. In Zambia, below ground surface mineral rights belong to the state. Given the global nature and scope of mining induced displacements and resettlements, micro-level dynamics easily remain invisible. In Zambia, research in lived experiences of displaced and resettled communities remain sparse and often unpublished. The aim of the research was to explore the psychological and socio-economic implications for the displaced and resettled households by a Nickel Mining Company in Mazabuka, southern Zambia. Families were purposively sampled and interviewed. Positive and negative lived experiences emerged from the interviews and have been presented as themes. Improved access to services; increased employment opportunities; improved production and acquisition of productive assets; and guaranteed security of land tenure and improved quality of houses were the positive lived experiences of resettled families. Negative lived experiences were: poor quality of soils; loss of locational advantage; emotional depression; discontinuation of gardening activities; and inability to buy drugs for livestock. The findings revealed that despite the cultural homogeneity of the sampled families, lived experiences after resettlement were different based on socio-economic situation of households. This was determined by who the head of the household was, literacy levels and family labour availability, because agriculture is the main livelihood activity. This research used a qualitative single case study approach to understand the ‘how, what and why’ of the lived experiences of the resettled families. It sought to respond to three related research questions: i) Did loss of access manifest in the studied case, and if so, how? What are the psychosocio-economic implications of the Munali Nickel mining-induced displacement and resettlement; ii) What characterizes the livelihoods of resettled families following the establishment of the Munali Nickel Mine, which assets were positively or negatively affected by resettlement and compensation; and iii) What are the coping mechanisms of the displaced and resettled communities following the establishment of the Munali Nickel Mine? The results of this research indicate that the level of compensation paid to resettled family cannot make up for what communities give up so that mining activities can start. Cultural values and the sense of belonging, for example are not compensated for when these are the factors that ensure psychological well-being of communities. Compensation and fulfillment of development promises were‘delayed and not necessarily denied.’ Access to education and health facilities was not achieved until nearly 10 years later, partially attributed to frequent closures of the mine that prevented the mine from honouring its promises in time. The uncertainty in the operations of the mine, loss of access to livelihood strategic resources was unsettling and created a sense of anxiety among resettled community members. While access to schools and clinics as physical assets was facilitated following resettling, the resettled community was not wholly part of the mining operation to the level that ensured human capacity development. For a highly technological undertaking as mining, resettled households could not benefit from any knowledge transfer. Furthermore, interviewed households reported increased distance to the tarred road; loss of sources of livelihood to closure of the mine, and loss of business opportunities in resettlement site; sub-standard houses with leaking roofs and cracks, as well as non-uniformity in compensation; inadequate grazing land; reduced agroproduction due to water logging in the fields and poor soils; scarcity of firewood; and nonreinstatement of churches, among negative experiences that they have lived. Coping with the experiences of ‘delay but not denial of access’ and a ‘mixed bag’ of changes to different asset classes was differential based on age, sex and household composition that determined the level of available labour in the household.